2014
DOI: 10.1002/bab.1236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyl jasmonate and salicylic acid on tanshinone production and biosynthetic gene expression in transgenic Salvia miltiorrhiza hairy roots

Abstract: Tanshinone is a group of active diterpenes, which are widely used in the treatment of cardiovascular disease. In this study, methyl jasmonate (MJ) and salicylic acid (SA) were used to investigate their effects on tanshinone accumulation and biosynthetic gene expression in the hairy roots of geranylgeranyl diphosphate synthase (SmGGPPS) overexpression line (G50) in Salvia miltiorrhiza. High-performance liquid chromatography analysis showed that total tanshinone content in G50 was obviously increased by 3.10-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 33 publications
4
112
0
1
Order By: Relevance
“…The case of Radix Salvia miltiorrhiza was used for demonstrating the potential application of this method. Substantial evidence has shown that Tanshinone IIA is one of the main pharmacologically active ingredients in Radix Salvia miltiorrhiza . Our radar chart analysis suggests that Tanshinone IIA is a typical strong retention compound in the C 18 column (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The case of Radix Salvia miltiorrhiza was used for demonstrating the potential application of this method. Substantial evidence has shown that Tanshinone IIA is one of the main pharmacologically active ingredients in Radix Salvia miltiorrhiza . Our radar chart analysis suggests that Tanshinone IIA is a typical strong retention compound in the C 18 column (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 69%
“…In this report, we found that SA and MeJA could increase accumulation of acteoside in R. glutinosa hairy roots, but SA was much more effective than MeJA in stimulating the accumulation of acteoside (Figure 1B). SA is a well-known inducer of plant systematic acquired resistance in plant-pathogen (Jian et al, 2005), and often used to improve the accumulation of plant secondary metabolites (Hao et al, 2014; Saini et al, 2014). The content of total PeG of C. deserticola cell cultures was obviously elevated by SA at concentration range of 10 ~ 100 μmol/L (Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonic acid (JA) can regulate the secondary metabolism in several plant species (De Geyter et al, 2012; Zhou and Memelink, 2016), including some traditional Chinese medicinal plants, like Scutellaria baicalensis (Zhao et al, 2016), Salvia miltiorrhiza (Hao et al, 2015), and Catharanthus roseus (van der Fits and Memelink, 2000). It is reported that the JA treatment could simultaneously stimulate artemisinin biosynthesis and promote the formation of glandular trichomes in A. annua (Maes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%